A water-stable inorganic sulfide electrolyte and its preparation method and battery
By using end-hydroxy-terminated polyoxysilane hydrophobic layer on the surface of the sulfide solid electrolyte, the problem of sulfide electrolyte sensitivity to water is solved, the humidity air stability and electrolyte performance are improved, and the cost and performance problems caused by doping elements are avoided.
Patent Information
- Application Number
- CN202410136704.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-01-31
AI Technical Summary
Existing sulfide solid electrolytes are sensitive to water and decompose to water to form toxic gases. When doped elements are used to improve the stability of wet air, it may affect the ion conductance of the electrolyte and increase costs.
The polyoxysilane with end hydroxyl-terminated end is used as the hydrophobic layer. Through the reaction with the sulfide electrolyte, the polyoxysilane is anchored to the surface of the electrolyte particles to block air and moisture, and improve the stability of the wet air.
It significantly improves the wet air stability of the sulfide solid electrolyte, avoids the risk of shedding, and improves the overall performance of the electrolyte without affecting ion conductance.
Smart Images

Figure BDA0004691512300000031 
Figure BDA0004691512300000032 
Figure BDA0004691512300000071
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a water-stable inorganic sulfide electrolyte and a preparation method thereof and a battery. Background Art
[0002] Lithium-ion secondary batteries play an extremely important role in modern society, especially the development of new energy vehicles and large-scale energy storage, which has pushed them to an unprecedented height. With the continuous improvement of the energy density and safety requirements of power batteries, the existing liquid lithium-ion battery system has approached the upper limit of energy density, and the flammable organic electrolyte makes the safety hazards of high-energy liquid lithium-ion batteries more prominent. All-solid-state batteries that use non-flammable inorganic solid materials as electrolytes can not only eliminate the safety hazards caused by organic electrolyte leakage and thermal runaway inside the battery during use, but also can be used under extreme conditions such as high and low temperatures. The use of lithium metal negative electrodes will also further improve the energy density of all-solid-state lithium secondary batteries. Solid electrolytes are the most critical materials in all-solid-state batteries. The development of inorganic solid electrolytes with high stability and high lithium ion conductivity is the key to the development of high-performance all-solid-state batteries.
[0003] Among many solid electrolyte materials, sulfide solid electrolytes are currently the most studied and have the greatest application potential. The main reason is that sulfide electrolytes have ion conductivity comparable to that of liquid electrolytes. However, sulfide solid electrolytes are sensitive to water and decompose into toxic H2S gas when in contact with water, resulting in a decrease in ionic conductivity. Therefore, the use conditions of sulfide solid electrolytes are very harsh, which is not conducive to large-scale application. Therefore, it is necessary to develop a sulfide electrolyte material that is stable to wet air to meet the needs of practical application. Using other elements to dope and replace elements such as P and S in sulfide solid electrolytes can effectively improve the wet air stability of sulfide solid electrolytes. Articles and invention patents have been reported, such as ACSSustainable Chem.Eng.2020,8,3321-3327, ACS Appl.Mater.Interfaces 2022,14,4179-4185, CN110085908A and CN113097560A. However, it still has certain limitations. The introduction of doping elements will inevitably affect the ion conductivity of the electrolyte material. The elements involved in the introduction of sulfide solid electrolytes are mainly Li, P, S, and halogen lamps, which are cheap elements. They are considered to have natural competitive advantages in terms of cost. Doping elements have caused their price advantages to disappear to a certain extent, which will inevitably limit their large-scale application. Some doping elements (As) are even toxic, which is obviously contrary to the green development path of lithium-ion batteries and new energy vehicles. Invention CN115377481A reports an organic-inorganic composite solid electrolyte. The shell polyurethane can improve the air stability of the core sulfide electrolyte. Its disadvantage is that the shell is too thick (30 to 50 μm). The polyurethane itself is an unstable organic matter and has a risk of fire when heated. It is contrary to the original intention of high safety of all-solid-state batteries. At the same time, the low ion conductivity shell will inevitably lead to a decrease in the overall ion conductivity of the electrolyte material. In addition, studies have shown that sulfide solid electrolytes have serious side reactions with polar solvents (such as Nano letters, 2017, 17, 3013-3020), so the method disclosed therein obviously cannot obtain high-performance electrolyte materials. Invention CN112018458A discloses an aqueous sulfide-polymer composite solid electrolyte, which is still an organic-inorganic composite in nature, and the template method cannot provide a powdered electrolyte material with wider applicability according to the use requirements of all-solid-state batteries. Invention CN111129579A discloses a sulfide solid electrolyte coated with a non-Li hydrophobic molecular layer, but the melting point of the alkyl phosphoric acid used is only about 100°C. When the operating temperature of the all-solid-state battery exceeds 100°C, there is a risk of coating failure. In addition, the above schemes cannot effectively solve the problem of close contact between the organic coating layer and the sulfide core, and there is a risk of shell shedding. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a water-stable inorganic sulfide solid electrolyte, i.e., stable under wet air conditions, and a preparation method and battery thereof. The present invention has found that the above technical difficulties can be solved by treating the sulfide solid electrolyte with polysiloxane terminated with terminal hydroxyl groups. The polysiloxane shell plays a role in blocking air and moisture. By utilizing the reaction between the terminal hydroxyl groups and the sulfide electrolyte, the polysiloxane can be anchored on the surface of the electrolyte particles, avoiding the risk of falling off; and the water stability (wet air stability) of the sulfide solid electrolyte has been significantly improved.
[0005] Specifically, the water-stable inorganic sulfide electrolyte provided in the first aspect of the present invention comprises an inorganic sulfide electrolyte material and a hydrophobic layer covering the surface of the inorganic sulfide electrolyte material; wherein the hydrophobic layer is a polysiloxane terminated with a terminal hydroxyl group, and the thickness of the hydrophobic layer is 1 to 20 nm. The present invention uses a polysiloxane terminated with a terminal hydroxyl group as the surface hydrophobic layer of the water-stable inorganic sulfide electrolyte. The polysiloxane shell plays a role in blocking air and moisture. At the same time, the terminal hydroxyl group reacts with the sulfide electrolyte, and the polysiloxane anchor can be well fixed on the surface of the electrolyte particles, avoiding the risk of falling off. The wet air stability of the sulfide solid electrolyte provided by the present invention has been significantly improved. The present invention has found that the effect is best when the thickness of the specific hydrophobic layer is in the range of 1 to 20 nm. If the thickness of the hydrophobic layer is too small, the water stability is not high, and if the thickness of the hydrophobic layer is too large, the ion conductivity of the sulfide is affected.
[0006] Preferably, the structural formula of the hydroxyl-terminated polysilane is as follows:
[0007]
[0008] Among them, R1 and R2 are each selected from one or more of halogen, methyl, methoxy, ethyl, ethoxy, vinyl, epoxy, amide, acyloxy, aminopropyl, and urea group, and R3 is selected from one or more of hydroxy, oxo, amino, trialkylsilyl, trialkoxysilyl, and alkoxy group, and n is an integer of 10 to 1000.
[0009] Or, the structural formula of the hydroxyl-terminated polysilane is as follows:
[0010]
[0011] Wherein, R4 is selected from one or more of F and CF3, R5 is selected from one or more of trialkylsilyl, trialkoxysilyl and alkoxy, and n is an integer of 10 to 1000.
[0012] More preferably, the hydrophobic layer has a thickness of 5 to 15 nm.
[0013] Preferably, the hydroxyl value of the terminal hydroxyl-terminated polyoxysilane is ≤10.0, preferably 1 to 8. The present invention has found that the surface hydrophobic treatment of the sulfide solid electrolyte using polyoxysilane containing halogen, methyl, methoxy, ethyl, ethoxy, vinyl, epoxy, amide, acyloxy, aminopropyl and / or ureido groups and alkoxy-terminated with hydroxyl, sulfhydryl, amino, trimethylsilyl and / or trimethoxysilyl groups can effectively improve its water stability. The reaction between the blocked terminal hydroxyl group and the sulfide solid electrolyte can ensure that the hydrophobic layer is tight and dense. When the hydroxyl value is ≤10.0, the reaction does not have a significant effect on the ion conductivity of the sulfide electrolyte, especially when the hydroxyl value of the terminal hydroxyl-terminated polyoxysilane is 1 to 8, the comprehensive performance is optimal.
[0014] The method of the present invention is not limited to the state of the inorganic sulfide electrolyte material, which can be an amorphous state, a glassy state, a crystalline state, or any combination of the three states.
[0015] Preferably, the number of carbon atoms in each of the substituents R1, R2, R3, R4, and R5 is ≤8.
[0016] In the present invention, the inorganic sulfide electrolyte material is a prepared inorganic sulfide electrolyte material or a commercial inorganic sulfide electrolyte material.
[0017] Further preferably, the inorganic sulfide electrolyte material contains P and / or halogen; the inorganic sulfide electrolyte material is amorphous, glassy, crystalline, or any combination of the three forms;
[0018] Preferably, the inorganic sulfide electrolyte material is in an argyrodite-type crystalline state.
[0019] More preferably, the inorganic sulfide electrolyte material is Li 6±a P 1-b M b S 5±a -cO c X d , wherein 0≤a<1.0, 0≤b<1.0, 0≤c<1.0, 0.6≤d≤2.0, M is selected from one or more of Ge, Si, Sn, Sb, Al, and X is selected from one or more of Cl, Br, and I.
[0020] The method for preparing the water-stable inorganic sulfide electrolyte provided in the second aspect of the present invention comprises:
[0021] 1) dispersing an inorganic sulfide electrolyte material in a first solvent to obtain a first dispersion;
[0022] 2) dissolving the hydroxyl-terminated polysilane in a second solvent to obtain a second dispersion;
[0023] 3) mixing the first dispersion and the second dispersion, and stirring at 25-70° C. for 30-120 min;
[0024] 4) removing the solvent to obtain a water-stable inorganic sulfide electrolyte.
[0025] Preferably, the first solvent is selected from one or more of a non-polar solvent, a polar solvent with a polarity not greater than 0.1, and a mixed solvent with a polarity not greater than 0.1; preferably, the first solvent is selected from one or more of isopentane, n-pentane, hexane, cyclohexane, isooctane and trimethylpentan;
[0026] And / or, the second solvent is selected from one or more of a non-polar solvent, a polar solvent with a polarity not greater than 0.2, and a mixed solvent with a polarity not greater than 0.2; preferably, the second solvent is selected from one or more of petroleum ether, trifluoroacetic acid, cyclopentane and n-heptane.
[0027] Further preferably, in step 1), the mass ratio of the inorganic sulfide electrolyte to the first solvent is (10-40):100;
[0028] And / or, in step 2), the mass ratio of the terminal hydroxyl-terminated polysiloxane to the second solvent is (0.5-10):100.
[0029] Preferably, in step 4), the method for removing the solvent comprises suction filtration; and / or vacuum heat treatment at a temperature of 80 to 120° C. for 8 to 24 hours.
[0030] In the present invention, the water-stable inorganic sulfide electrolyte prepared by the above-mentioned process and preferred conditions further improves the water stability and cycle performance.
[0031] The present invention also provides the use of any of the above sulfide solid electrolytes in the preparation of an all-solid-state lithium secondary battery.
[0032] The third aspect of the present invention also provides a lithium secondary battery, comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, wherein the lithium secondary battery contains a water-stable inorganic sulfide electrolyte prepared by the above-mentioned water-stable inorganic sulfide electrolyte or any one of the above-mentioned methods for preparing water-stable inorganic sulfide electrolyte materials. In the present invention, the lithium secondary battery prepared by using the terminal hydroxyl-terminated polysiloxane is more stable during use and has excellent performance. After a long cycle, the battery using the sulfide solid electrolyte of the present invention shows a more excellent cycle performance.
[0033] The beneficial effects of the present invention are at least:
[0034] 1) The end-hydroxyl-terminated polyoxysilane provided by the present invention treats the sulfide solid electrolyte. The polyoxysilane shell acts as a barrier to air and moisture. By using the reaction between the end-hydroxyl group and the sulfide electrolyte, the polyoxysilane can be better anchored on the surface of the electrolyte particles. At the same time, the wet air stability of the sulfide solid electrolyte is significantly improved.
[0035] 2) The present invention has a wide range of application and can be used in various solid electrolyte materials containing S elements, and does not limit the crystal form of the sulfide electrolyte. It is suitable for the preparation of sulfide electrolytes, and is also suitable for the further treatment of commercially purchased sulfide electrolyte materials. The preparation method is simple, efficient and low-cost.
[0036] 3) The proposal and acquisition of the water-stable sulfide solid electrolyte of the present invention is conducive to understanding and further improving the stability of the electrolyte in theoretical research. In practical applications, a variety of different types of high-stability electrolyte materials can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the accompanying drawings that need to be used in the embodiment or the prior art description will be briefly introduced below. It will be obvious that the accompanying drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings can also be obtained based on these accompanying drawings without expending creative labor.
[0038] Figure 1 This is a TEM image of the solid electrolyte material obtained in Example 1 of the present invention;
[0039] Figure 2 XRD diffraction patterns of the solid electrolyte materials obtained in Example 1 and Comparative Example 1 of the present invention;
[0040] Figure 3 The battery cycle performance of the sulfide solid electrolyte of the solid electrolyte material provided in Example 1 and Comparative Example 11 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] If no specific technology or conditions are specified in the examples of the present invention, the technology or conditions described in the literature in the field or the product instructions shall be followed. If the manufacturer of the devices, instruments, reagents, etc. used is not specified, they are all conventional products that can be purchased through regular channels. The raw materials used in the present invention can be easily purchased in the domestic product market. The terminal hydroxyl-terminated polysiloxanes used in the examples of the present invention and the comparative examples are all purchased from the domestic product market. The structural formula of the terminal hydroxyl-terminated polysiloxane is formula (1):
[0043]
[0044] Among them, R1 and R2 are each selected from one or more of halogen, methyl, methoxy, ethyl, ethoxy, vinyl, epoxy, amide, acyloxy, aminopropyl, and urea groups, and R3 is selected from one or more of hydroxy, oxo, amino, trialkylsilyl, trialkoxysilyl, and alkoxy groups, and n is an integer of 10 to 1000;
[0045] Or the structural formula of the hydroxyl-terminated polysilane is as follows:
[0046]
[0047] Wherein, R4 is selected from one or more of F and CF3, R5 is selected from one or more of trialkylsilyl, trialkoxysilyl and alkoxy, and n is an integer of 10 to 1000.
[0048] Example 1
[0049] This embodiment provides a water-stable inorganic sulfide electrolyte and a preparation method thereof.
[0050] The sulfide solid electrolyte material used was prepared as follows: In a glove box, press Li 5.5 PS 4.5 Cl 1.5 Weigh Li2S, P2S5, and LiCl according to the proportion of elements in the mixture. Place the above raw materials in a 50ml zirconia ball mill and add 50g of 5mm diameter zirconia balls. Place the sealed ball mill on the ball mill and grind and mix evenly. Collect the ball-milled samples and seal them in a vacuum quartz tube for calcination. The calcination temperature is controlled by programmed temperature rise, rising from room temperature to 540°C at a rate of 3°C / min and keeping warm for 12h. After sintering, cool to 50°C to obtain the target sulfide solid electrolyte material Li 5.5 PS 4.5 Cl 1.5, it is a crystalline state of sulfur silver germanium ore type. (The embodiment of the present invention is only one of the conventional preparation methods for explaining the sulfide solid electrolyte material, and is not used to limit the sulfide solid electrolyte material used in the present invention. The sulfide solid electrolyte material used in the present invention can be obtained in any manner).
[0051] The sulfide solid electrolyte material is dispersed in cyclohexane, and the mass ratio of the electrolyte to the solvent is 20:100, to obtain a dispersion 1;
[0052] The end-hydroxy-terminated polyoxysilane represented by formula 1 used in this example in Table 1 was dispersed in n-heptane, and the mass ratio of the end-hydroxy-terminated polyoxysilane to the solvent was 0.8:100 to obtain dispersion 2; the concentration ratio of dispersion 2 and dispersion 1 was 4.0:100;
[0053] Dispersion 1 and dispersion 2 were mixed in a ratio of 1:1, stirred at 60°C for 60 minutes, and after stirring, most of the solvent was removed by suction filtration, and then heated in a vacuum oven at 115°C for 24 hours to obtain the target electrolyte material with a thickness of 12 nm in a hydrophobic layer. The TEM image of the solid electrolyte material obtained in this embodiment is as Figure 1 As shown, the coating layer of the solid electrolyte material is in close contact with the electrolyte, and the XRD diffraction pattern of the solid electrolyte material is as shown Figure 2 shown.
[0054] Example 2
[0055] The same method as in Example 1 was used, except that the hydroxyl-terminated polysilane used in Table 1 was different to obtain a target electrolyte material with a hydrophobic layer thickness of 12 nm.
[0056] Example 3
[0057] The same method as in Example 1 is adopted, except that the sulfide solid electrolyte material is dispersed in cyclohexane, and the mass ratio of the electrolyte to the solvent is 35:100, to obtain a dispersion 1;
[0058] The end-hydroxy-terminated polyoxysilane used in this example in Table 1 was dispersed in n-heptane, and the mass ratio of the end-hydroxy-terminated polyoxysilane to the solvent was 1.0:100 to obtain dispersion 2; the concentration ratio of dispersion 2 and dispersion 1 was 2.9:100;
[0059] Dispersion 1 and dispersion 2 were mixed in a ratio of 1:1, stirred at 60°C for 60 minutes, after stirring, most of the solvent was removed by suction filtration, and then heated in a vacuum oven at 115°C for 24 hours to obtain the target electrolyte material with a thickness of 8 nm in a hydrophobic layer.
[0060] Example 4
[0061] The same method as in Example 1 is adopted, except that the sulfide solid electrolyte material is dispersed in trimethylpentane, and the mass ratio of the electrolyte to the solvent is 15:100, to obtain a dispersion 1;
[0062] The end-hydroxy-terminated polyoxysilane used in this example in Table 1 was dispersed in n-heptane, and the mass ratio of the end-hydroxy-terminated polyoxysilane to the solvent was 0.7:100 to obtain dispersion 2; the concentration ratio of dispersion 2 and dispersion 1 was 4.7:100;
[0063] Dispersion 1 and dispersion 2 were mixed in a ratio of 1:1, stirred at 60°C for 60 minutes, and after stirring, most of the solvent was removed by suction filtration, and then heated in a vacuum oven at 115°C for 24 hours to obtain the target electrolyte material with a thickness of 14 nm in a hydrophobic layer.
[0064] Example 5
[0065] The same method as in Example 1 is adopted, except that the sulfide solid electrolyte material is dispersed in isooctane, and the mass ratio of the electrolyte to the solvent is 40:100, to obtain a dispersion 1;
[0066] The end-hydroxy-terminated polyoxysilane used in this example in Table 1 was dispersed in n-heptane, and the mass ratio of the end-hydroxy-terminated polyoxysilane to the solvent was 0.5:100 to obtain dispersion 2; the concentration ratio of dispersion 2 and dispersion 1 was 1.25:100;
[0067] Dispersion 1 and dispersion 2 were mixed in a ratio of 1:1, stirred at 60°C for 60 minutes, and after stirring, most of the solvent was removed by suction filtration, and then heated in a vacuum oven at 115°C for 24 hours to obtain the target electrolyte material with a thickness of 6 nm in a hydrophobic layer.
[0068] Example 6
[0069] The same method as in Example 1 was used, the difference was that the terminal hydroxyl-terminated polyoxysilane was used, and the solvent of the dispersion 2 was replaced with trifluoroacetic acid. The target electrolyte material having a hydrophobic layer thickness of 12 nm was obtained.
[0070] Example 7
[0071] The same method as in Example 1 was used, except that the polysilane terminated with terminal hydroxyl groups was different, to obtain the target electrolyte material with a hydrophobic layer thickness of 12 nm.
[0072] Example 8
[0073] The same method as in Example 1 is adopted, except that the sulfide solid electrolyte is replaced with Li6PS5Cl to obtain a target electrolyte material with a hydrophobic layer thickness of 12 nm.
[0074] Example 9
[0075] The same method as in Example 1 is used, except that the sulfide solid electrolyte is replaced with Li6P 0.95 Sn 0.05 S5Cl. The target electrolyte material with a hydrophobic layer thickness of 12 nm was obtained.
[0076] Example 10
[0077] The same method as in Example 1 is used, except that the sulfide solid electrolyte is replaced with Li6P 0.98 Sn 0.02 S 4.98 O 0.02 The target electrolyte material with a hydrophobic layer thickness of 12 nm was obtained.
[0078] Comparative Examples 1-10
[0079] The same method as in Example 1 was used, except that the polysilane terminated with terminal hydroxyl groups was different, and its R1, R2, and R3 groups were shown in Table 1. The target electrolyte material with a hydrophobic layer thickness of 12 nm was obtained.
[0080] Comparative Example 11
[0081] The same method as in Example 1 is adopted, except that the hydroxyl-terminated polysiloxane is replaced with: The substituents of R1, R2 and R3 are shown in Table 1.
[0082] Comparative Example 12
[0083] The same method as in Example 1 is used, except that the terminal hydroxyl-terminated polysiloxane is different. The mass ratio of the terminal hydroxyl-terminated polysiloxane to the solvent is 1.7:100, to obtain dispersion 2; the concentration ratio of dispersion 2 to dispersion 1 is 8.5:100;
[0084] Dispersion 1 and dispersion 2 were mixed in a ratio of 1:1 and stirred at 60°C for 60 min. After stirring, most of the solvent was removed by filtration, and then heated in a vacuum oven at 115°C for 24 h to obtain the target electrolyte material with a hydrophobic layer thickness of 25 nm.
[0085] Examples 11-19
[0086] The same method as in Example 1 was used, except that a different hydroxyl-terminated polysilane of formula (2) was used, and its R4, R5 groups, n value, and hydroxyl value were shown in Table 2. A target electrolyte material with a hydrophobic layer thickness of 12 nm was prepared.
[0087] Comparative Examples 12-17
[0088] The same method as in Example 1 was used, except that a different hydroxyl-terminated polysilane of formula (2) was used, and its R4, R5 groups, n value, and hydroxyl value were shown in Table 2. A target electrolyte material with a hydrophobic layer thickness of 12 nm was prepared.
[0089] Experimental Example 1
[0090] Wet air stability test of solid electrolyte materials
[0091] The obtained solid electrolyte material was subjected to a wet air stability test. In a glove box, 300 mg of the solid electrolyte material was weighed and placed in a 5 ml open glass bottle. The glass bottle was then placed in a reaction box with a specific humidity air flow and allowed to stand at room temperature. The relative humidity of the dry air was 10% and the air flow rate was 100 ml / min. After 24 hours, samples were taken for ion conductivity testing. The data of each embodiment and comparative example are summarized in Table 1 and Table 2.
[0092] Table 1 Data summary of Examples 1 to 10 and Comparative Examples 1 to 12
[0093]
[0094]
[0095] Table 2 Data summary of Examples 11 to 19 and Comparative Examples 1 to 4, 13 to 18
[0096]
[0097] It can be found from Table 1 and Table 2 that the sulfide solid electrolyte material treated with the end hydroxyl-terminated polysiloxane provided by the present invention has only a slight decrease in ion conductance compared with the untreated bare sample, but the decrease after exposure to humid air is greatly reduced, that is, the water stability is greatly improved. When the end hydroxyl-terminated polysiloxane and its substituents are not required in the present invention, the ion conductance decreases by a large margin, and the water stability is not significantly improved compared with the untreated sulfide solid electrolyte material (Comparative Example 1). When the thickness of the surface coating layer is >20nm (Comparative Example 12), although its stability can be guaranteed, the ion conductance decreases by too much (5.84→3.22mS / cm) compared with the bare sample without coating treatment.
[0098] The material composition of the invention is simple, the raw materials are easily available, the preparation method is simple, the production cost is low, and at the same time it has good air stability and high lithium ion conductivity, and is expected to solve the practical application problem of inorganic sulfide electrolytes as high-performance all-solid-state lithium secondary battery electrolytes.
[0099] The coating layer of the sulfide solid electrolyte material provided in the embodiment of the present invention has good stability during use, and the all-solid-state lithium secondary battery provided by the sulfide solid electrolyte material shows better cycle performance than the prior art after a long cycle. Taking Example 1 as an example, the sulfide solid electrolytes of Example 1 and Comparative Example 11 are used as the solid electrolyte layer, respectively, and LiNi 0.90 Co 0.05 Mn 0.05 The mixture of O2 ultra-high nickel oxide positive electrode and Example 1 or Comparative Example 11 is used as the positive electrode layer, and Li-In alloy is used as the negative electrode layer to assemble an all-solid-state lithium secondary battery.
[0100] The charge and discharge cycle test was carried out with a charge and discharge current of 0.1C and a voltage range of 2.5-4.3V (vs. Li / Li + ), the temperature is room temperature (25°C).
[0101] The results show that although the electrolyte materials of Example 1 and Comparative Example 11 have very similar ion conductance and wet air stability, and the first 10 cycles of the mold batteries using the two electrolytes are basically the same, after a long cycle, the battery using the sulfide solid electrolyte of the present invention shows a more excellent cycle performance ( Figure 3 ). This indicates that the coating layer of the sulfide solid electrolyte material of the present invention is more stable during use.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A water-stable inorganic sulfide electrolyte, characterized in that: It comprises an inorganic sulfide electrolyte material and a hydrophobic layer covering the surface of the inorganic sulfide electrolyte material; wherein the hydrophobic layer is a polysilane terminated with a terminal hydroxyl group, and the thickness of the hydrophobic layer is 1 to 20 nm; The structural formula of the hydroxyl-terminated polysilane is as follows: Wherein, R1 and R2 are each selected from one or more of halogen, methyl, methoxy, ethyl, ethoxy, vinyl, epoxy, amide, acyloxy, aminopropyl, and urea, and R1 and R2 are not methyl at the same time, R3 is selected from one or more of mercapto, amino, trialkylsilyl, trialkoxysilyl, and alkoxy, and n is an integer of 10 to 1000; Or, the structural formula of the hydroxyl-terminated polysilane is as follows: Wherein, R4 is selected from one or more of F and CF3, R5 is selected from one or more of trialkylsilyl, trialkoxysilyl and alkoxy, and n is an integer of 10 to 1000; The hydroxyl value of the terminal hydroxyl-terminated polysilane is 1-8.
2. The water-stable inorganic sulfide electrolyte according to claim 1, characterized in that The number of carbon atoms in each of the substituents R1, R2, R3, R4, and R5 is ≤8.
3. The water-stable inorganic sulfide electrolyte according to claim 1, characterized in that The inorganic sulfide electrolyte material contains P and / or halogen; the inorganic sulfide electrolyte material is in an amorphous state, a glassy state, a crystalline state, or any combination of the three forms.
4. The water-stable inorganic sulfide electrolyte according to claim 3, characterized in that The inorganic sulfide electrolyte material is in a crystalline state of argyrodite; And / or, the inorganic sulfide electrolyte material is Li 6±a P 1-b M b S 5±a-c O c X d , wherein 0≤a<1.0, 0≤b<1.0, 0≤c<1.0, 0.6≤d≤2.0, M is selected from one or more of Ge, Si, Sn, Sb, Al, and X is selected from one or more of Cl, Br, and I.
5. The method for preparing the water-stable inorganic sulfide electrolyte according to any one of claims 1 to 4, characterized in that: include: 1) dispersing an inorganic sulfide electrolyte material in a first solvent to obtain a first dispersion; 2) dissolving the hydroxyl-terminated polysiloxane in a second solvent to obtain a second dispersion; 3) mixing the first dispersion and the second dispersion, and stirring at 25-70° C. for 30-120 min; 4) removing the solvent to obtain a water-stable inorganic sulfide electrolyte.
6. The method for preparing a water-stable inorganic sulfide electrolyte according to claim 5, characterized in that: The first solvent is selected from one or more of a non-polar solvent, a polar solvent with a polarity not greater than 0.1, and a mixed solvent with a polarity not greater than 0.1; And / or, the second solvent is selected from one or more of a non-polar solvent, a polar solvent with a polarity not greater than 0.2, and a mixed solvent with a polarity not greater than 0.
2.
7. The method for preparing a water-stable inorganic sulfide electrolyte according to claim 6, characterized in that: The first solvent is selected from one or more of isopentane, n-pentane, hexane, cyclohexane, isooctane and trimethylpentane; And / or, the second solvent is selected from one or more of petroleum ether, trifluoroacetic acid, cyclopentane and n-heptane.
8. The method for preparing a water-stable inorganic sulfide electrolyte according to any one of claims 5 to 7, characterized in that: In step 1), the mass ratio of the inorganic sulfide electrolyte to the first solvent is (10-40):100; And / or, in step 2), the mass ratio of the terminal hydroxyl-terminated polysiloxane to the second solvent is (0.5-10):
100.
9. The method for preparing a water-stable inorganic sulfide electrolyte according to any one of claims 5 to 7, characterized in that: In step 4), the method for removing the solvent includes suction filtration; and / or vacuum heat treatment at a temperature of 80 to 120° C. for 8 to 24 hours.
10. A lithium secondary battery comprising a positive electrode layer, a negative electrode layer and a solid electrolyte layer, characterized in that: The lithium secondary battery contains a water-stable inorganic sulfide electrolyte prepared by the water-stable inorganic sulfide electrolyte according to any one of claims 1 to 4 or the method for preparing a water-stable inorganic sulfide electrolyte according to any one of claims 5 to 9.
Citation Information
Patent Citations
Sulfide solid electrolyte material, preparation method thereof and solid-state battery
CN111129579A
Sulfide-polymer composite solid electrolyte, preparation method and application thereof
CN112018458A
Nanocrystalline sulfide solid electrolyte with high air stability, preparation method thereof, solid-state battery and preparation method of solid-state battery
CN113097560A
Organic-inorganic composite solid electrolyte, preparation method thereof and lithium ion solid-state battery
CN115377481A
In-situ formed sulfide composite solid electrolyte and preparation method thereof
CN112909322A